Direct and indirect effects of investment incentives in Slovakia - Aneta Bobenič Hintošová; František Sudzina; Terézia Barlašová (Journal of Risk and Financial Management, 2021)
Countries trying to attract foreign direct investment often use various tools to influence the foreign investor's allocation decision including public subsidies in the form of investment incentives. However, the effects associated with providing these incentives are often questioned, especially in light of the need to achieve at least a minimum level of attractiveness of the business environment. The primary aim of the present study was to examine the effects of investment incentives on foreign direct investment inflows (direct effect) and on selected macroeconomic variables (indirect effects) under the conditions in Slovakia. Findings showed that the preference of specific forms of investment incentives by the government of the Slovak Republic changed slightly in the observed period of 2002-2019. The results of the regression analysis further suggest that while financial incentives have a positive statistically significant direct effect on foreign direct investment inflows, in the case of fiscal incentives, this effect is the opposite. In terms of indirect effects of investment incentives, only a reduction in the unemployment rate through foreign direct investment was found. The study contributes to the literature by providing evidence on the effects of various forms of investment incentives and by offering some implications for investment promotion policy.
Keywords: 330; economic freedom; financial incentives; fiscal incentives; foreign direct investment; investment incentives; Slovakia